Proinflammatory cytokines in the prefrontal cortex of teenage suicide victims - Pandey, Ghanshyam N.; Rizavi, Hooriyah S.; Ren, Xinguo; Fareed, Jawed; Hoppensteadt, Debra A.; Roberts, Rosalinda C.; Conley, Robert R.; Dwivedi, Yogesh (Journal of psychiatric research, 2012)
Teenage suicide is a major public health concern, but its neurobiology is not well understood. Proinflammatory cytokines play an important role in stress and in the pathophysiology of depression—two major risk factors for suicide. Cytokines are increased in the serum of patients with depression and suicidal behavior; however, it is not clear if similar abnormality in cytokines occurs in brains of suicide victims. We therefore measured the gene and protein expression levels of proinflammatory cytokines interleukin (IL)-1β, IL-6, and tissue necrosis factor (TNF)-α in the prefrontal cortex (PFC) of 24 teenage suicide victims and 24 matched normal control subjects. Our results show that the mRNA and protein expression levels of IL-1β, IL-6, and TNF-α were significantly increased in Brodmann area 10 (BA-10) of suicide victims compared with normal control subjects. These results suggest an important role for IL-1β, IL-6, and TNF-α in the pathophysiology of suicidal behavior and that proinflammatory cytokines may be an appropriate target for developing therapeutic agents.